Short Communication: Agalmyla inaequidentata Hilliard & B.L. Burtt (Gesneriaceae- Didymocarpoideae): A new genus record for Buru Island, Maluku, Indonesia - WENDY ACHMMAD MUSTAQIM (Society for Indonesian Biodiversity, 2017)
Mustaqim WA. 2017. Short Communication: Agalmyla inaequidentata Hilliard & B.L. Burtt (Gesneriaceae, Trichosporeae, Didymocarpinae): A new genus record in Buru Island, Maluku, Indonesia. Biodiversitas 18: 1062-1065. Agalmyla inaequidentata Hilliard & B.L. Burtt (Gesneriaceae, Didymocarpoideae) has been discovered for the first time on Buru Island, the first record of the genus on the island. The result expands the distribution of the genus in the Maluku, so that it is now present on the Halmahera, Buru and Seram, the three largest islands in the archipelago. This species differs from other members of Agalmyla by the presence of both globular glands and acute hairs on the ovary and style. The number of lateral veins of this species is now also extended from 4?6 to 4?9 on each side of the midrib.